Модернизация процесса ректификации частично растворимой азеотропной смеси фурфурол-вода - Бабак, Татьяна Геннадиевна; Голубкина, Ольга Александровна; Малышко, Юрий Валериевич; Пономаренко, Евгения Дмитриевна (НТУ "ХПИ", 2016)
Проведен анализ способов разделения азеотропных бинарных смесей. Проведено обследование ректификационной установки для разделения частично растворимой смеси фурфурол-вода. Определены характеристики тепловых потоков системы и на основе принципов пинч-анализа предложено решение по модернизации установки с целью минимизации потребления внешних утилит для экономически обоснованного значения минимального температурного напора в теплообменном оборудовании, Tmin. Подобраны пластинчатые теплообменные аппараты для рекуперации энергии.

The analysis of methods of binary azeotropes separation was carried out in the article. The inspection of the rectifier for separation of partially soluble mixture furfural-water was made. Characteristics of thermal streams of the system were determined, and the solution of modernization based on the pinch-analysis principles was offered with purpose of external utilities consumption minimization according to economically reasonable the value of the minimum temperature difference in the heat exchange equipment Tmin. Plate heat exchanges were recommended for energy recovery
Modernization of partially soluble mixture furfural-water rectification
Keywords: пинч-анализ; сеточная диаграмма; пластинчатые теплообменники; теплообменное оборудование; rectification; azeotrope; pinch-analysis; grid diagram; plate heat exchanges